The Role Of Titles Funcation In Embodyment Of The Texts Meaning Is Short Story Selectedshort Story - Taher, Nazar S. (Humanities Journal of University of Zakho, 2015)
The study tries to investigate the function of title in order to embody the meaning and the implicit meaning in the short story. The study also tries to enrich the Kurdish literary criticism with modern literary criticism theories. The title in the creative literary text represents the first relationship between the receiver and text and thus the receiver begins to create a primary idea from aesthetic and intellectual aspects of the signs of the text.In this study titled “The title’s function in embodiment of the short story –In the short stories collection named (The night of fleeing of the Angels) by Isammeel Hajany, and after showing a background about the title, the researcher has analyzed the main title for the chosen short stories where the signs reflected in seven titles and thirteen titles didn’t embody their implied meanings in the main title of the collection.